Polyphenol oxidase genes in barley (Hordeum vulgare L.): functional activity with respect to black grain pigmentation - Glagoleva, Anastasiia Y.; Kukoeva, Tat’jana V.; Khlestkina, Elena K.; Shoeva, Olesya Y. (Frontiers in Plant Science, 2024)
Polyphenol oxidase (PPO) is an oxidoreductase. In damaged plant tissues, it catalyzes enzymatic browning by oxidizing o-diphenols to highly reactive o-quinones, which polymerize producing heterogeneous dark polymer melanin. In intact tissues, functions of PPO are not well understood. The aim of the study was to investigate the barley PPO gene family and to reveal the possible involvement of Ppo genes in melanization of barley grain, which is controlled by the Blp1 gene. Based on known barley Ppo genes on chromosome 2H (Ppo1 and Ppo2), two additional genes-Ppo3 and Ppo4-were found on chromosomes 3H and 4H, respectively. These genes have one and two exons, respectively, contain a conserved tyrosinase domain and are thought to be functional. Comparative transcriptional analyses of the genes in samples of developing grains (combined hulls and pericarp tissues) were conducted in two barley lines differing by melanin pigmentation. The genes were found to be transcribed with increasing intensity (while grains mature) independently from the grain color, except for Ppo2, which is transcribed only in black-grained line i:BwBlp1 accumulating melanin in grains. Analysis of this gene's expression in detached hulls and pericarps showed its elevated transcription in both tissues in comparison with yellow ones, while it was significantly higher in hulls than in pericarp. Segregation analysis in two F2 populations obtained based on barley genotypes carrying dominant Blp1 and recessive ppo1 (I) and dominant Blp1 and recessive ppo1 and ppo2 (II) was carried out. In population I, only two phenotypic classes corresponding to parental black and white ones were observed; the segregation ratio was 3 black to 1 white, corresponding to monogenic. In population II, aside from descendants with black and white grains, hybrids with a gray phenotypelight hulls and dark pericarpwere observed; the segregation ratio was 9 black to 3 gray to 4 white, corresponding to the epistatic interaction of two genes. Most hybrids with the gray phenotype carry dominant Blp1 and a homozygous recessive allele of Ppo2. Based on transcription and segregation assays one may conclude involvement of Ppo2 but not Ppo1 in melanin formation in barley hulls.